Analisis Tingkat Ketergantungan Mahasiswa terhadap Penggunaan Pembayaran Digital dalam Transaksi Harian - Putri, Devita Mutiara; Nurmadiyyah, Zahra Nafisah; Setiyaningsih, Sri Isnani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the level of student dependency on digital payment usage in daily transactions. The rapid development of financial technology has significantly transformed payment systems, especially among university students as digital natives. This research applies a quantitative approach using a survey method with 52 student respondents. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics. The results show that students demonstrate a high level of usage of digital payments, mainly influenced by convenience, speed, and accessibility. However, psychological dependency is categorized as moderate. These findings indicate that although digital payment usage is high, dependency is not yet critical. Therefore, improving financial literacy is essential to ensure responsible usage.